Analisis Penerapan Akuntansi Berdasarkan SAK ETAP: Studi Kasus pada Koperasi Karyawan PT. Chandra Asri Petrochemical Tbk - Annissa Pratiwi (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to analyze the presentation and preparation of the financial statements PT. Chandra Asri Petrochemical Tbk, Cooperative in accordance with the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). This study uses a qualitative method with a descriptive analysis approach, primary data collection techniques through observation, interviews, and documentation, and secondary data techniques through information sources on the structure, history, and financial statements of the Employee Cooperative of PT. Chandra Asri Petrochemical Tbk. The results of this study indicate that the Financial Statements of the Employee Cooperative of PT. Chandra Asri Petrochemical Tbk are in accordance with the applicable SAK ETAP.